Analisis Kemampuan Berpikir Kritis dalam Menyelesaikan Soal Materi Program Linier - Fitri, Rinil; Rochaminah, Sutji; Hasbi, Muh; Baharuddin, Baharuddin (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to describe the critical thinking abilities of SMA Negeri 5 Model Palu students, especially in Linear program material. This research is descriptive research with a qualitative approach. The subjects in the research were students with high, medium and low mathematics abilities obtained from the results of report cards who were then given a critical thinking ability test. The research was conducted by interviewing students' test results and conducting time triangulation. The results obtained show that students with high ability fulfill all the indicators of interpretation, analysis, evaluation and inference, while students with medium ability only do not meet one indicator, namely inference, and students with low ability only master two indicators of critical thinking, interpretation and analysis abilities. In conclusion, with the differences in students' critical thinking abilities, teachers should pay attention to the differences in students' abilities to think critically in learning, in this case linear programming. Keywords: Critical Thinking Ability, Linear Program Material